PERTIMBANGAN HAKIM DALAM TINDAK PIDANA ANAK KORBAN KEKERASAN DAN PENCABULAN (PUTUSAN NO 189/PID.SUS/2021/PN SNT) - Robert Chandra Sadewa; Arsyad Aldyan (Sebelas Maret University, 2023)
Abstract: This study aims to determine the suitability of the judge's consideration in deciding the Violence and Child Molestation Case in accordance with Article 183 of the Criminal Procedure Code and whether the judge's decision is in accordance with the ideality of justice in Indonesia. This research is a descriptive normative legal research. The technique of collecting primary and secondary legal materials used is by studying documents or library materials. Based on the results of research and discussion, it can be seen that the reason for the Panel of Judges to impose the maximum verdict is that the Panel of Judges determined that the Defendant made threats of violence and forced the Child to commit obscene acts. Based on the results of research and discussion, it can be seen that the determination of the Defendant is valid because according to the author there is a suitability of valid evidence to strengthen the position of valid evidence as stated in Article 183 and Article 184 paragraph 1 of the Criminal Procedure Code. Based on the results of research and discussion in this case, the author also sees and looks at the decision issued by the Panel of Judges which according to the author isin accordance with the ideality of legal justice in Indonesia. Keywords: Crime of Violence and Child Molestation, Judges' Legal Considerations, Ideality of Justice